Cytokine Genetic Polymorphism of Interleukin-4 and Risk of Asthma in Some Iraqi Patients - Alaa Jawad Naif; Israa Adnan Ibraheam (Medical Journal of Babylon)
Background:Asthma, a chronic inflammatory respiratory disorder, is influenced by genetic and environmental factors. Allergic asthma is becoming more common because of higher levels of air pollution. Interleukin-4 (IL-4) plays an important role in allergic inflammation and causes the expression of vascular cell adhesion molecule-1. Objective:The present study aims to shed light on the association between cytokine genetic polymorphisms and asthma in Iraqi patients, and to determine their impact on the risk of disease, under the scope of the following: (1) IL-4 cytokines, in terms of their serum level. (2) Assessment of the polymorphisms in the promoter regions of the IL-4, genes in asthma disease patients was carried out, and then their impact on the profile of investigated cytokines was evaluated. Such a collective evaluation may aid in a better understanding of etiopathogenesis in the asthma disease. Materials and Methods:A case-control study was conducted that included 100 participants divided into a patient group (n = 50) with bronchial asthma and a healthy group as a control (n = 50) without asthma. Blood specimens were collected from participants at Marjan Hospital, Babylon Governorate. Serum levels of IL-4 were estimated by an enzyme-linked immunosorbent assay (ELISA) kit. IL4-590 gene polymorphism was detected using amplification refractory mutation system polymerase chain reaction (PCR) with specific primer sequences. Results:The mean concentrations of serum IL-4 were significantly higher in patients having asthma compared to the healthy group (149.84 vs. 53.50, P < 0.0001). In terms of allele and genotype frequencies, the TT genotype was shown to be less common in asthma group compared to controls (4% vs. 22%), whereas the CT genotype was more common in asthma patients (34% vs. 16%). The CC genotype was similar between the two groups. The T allele was more frequent in healthy (39%) compared to asthmatic group (12%), whereas the C allele frequency was higher in asthma patients (61%) compared to controls (88%). Conclusion:This study suggests that gene polymorphism of IL4-590 is associated with risk of developing asthma. Asthma patients have elevated levels of IL-4 and a lower frequency of the TT genotype, indicating an increased likelihood of developing asthma when carrying the T allele and TT genotype. Conversely, the C allele may have a protective influence against asthma development.